Dimensionamento de uma estação de tratamento de água (ETA) para os bairros atendidos pelo sistema de abastecimento do Sítio Deus é Grande no município de Tucuruí-PA - FURTADO, Erlen Freitas (2023)
The design of a Water Treatment Station (ETA) is the realization of an engineering project through the necessary calculations and following all the guidelines and rules imposed by the Brazilian Association of Technical Standards (ABNT). Thus, water is one of the most important resources of the ecosystem, in which it has several purposes, however, with regard to human consumption it must be free of pathogenic organisms and substances harmful to health, otherwise water is a potential source of transmission of various diseases. It is also emphasized the importance of its conscious and sustainable use, as a way to ensure the resource in the face of population expansion and the consequent increase in consumption. All individuals have needs of this resource with quality and sufficient quantity, not only for the protection of their health, but also for economic development. However, the importance of water supply must be seen in social, sanitary and economic aspects. Given the conditions of water collection that is distributed to the population within the municipality and because there are no studies and analyses on the physical, chemical and microbiological quality of that water body, we opted for a complete or conventional cycle treatment because it is a satisfactory, efficient and widely used process in Brazil. Therefore, the objective of this project was to propose the design of a Water Treatment Station for the neighborhoods served by the supply system of place God is Great, that is, stages of clarification and disinfection of water, using a project flow of 265 l/s, based on legal determinations and parameters established by the environmental legislation of the National Environmental Council (CONAMA), as well as Resolutions No. 430/2011, Ordinance No 888/2021, according to the recommendations of ABNT, NBR 10.004/2004, NBR 12.216/1992 that regulates through suggestions and rules how to carry out such project.